The Influence of Mental Maps Strategy on Students' Cognitive Achievement and Learning the skills of defense and attack in Fencing for Girl Students - Namoos Khalaf Al-Taie, Dhafer; Nadeem Ahmed, Maysaa (International Journal of Psychosocial Rehabilitation, 2020)
The researcher applied experimental methodology to a sample of thirty tertiary-level students from Physical Education and Sport Science College at the University of Diyala to identify the influence of mental maps strategy on students' cognitive achievement and learning offensive and defensive skills in fencing. Having done the main experiment, pretests and post-tests and data processing statistics, the study's main findings were: the experiment's results proved that students were able to retrieve responses effectively from the mental map; the mental maps helped the students to better understand cognitive information; and the students stated that mental maps enabled them to recall and understand information in a better and faster way. Therefore, the researcher recommends the following: the importance of utilizing mental maps strategy in learning offensive and defensive skills in fencing and academic disciplines due to its positive influence on students. Furthermore, it is viable to conduct similar research to study the influence of mental maps strategy on learning the rest of fencing basic skills and other academic disciplines using a sample of students.